Experimental study of the laser beam cutting on acrylic sheet - Mohd Aiman, Ismail (2009)
In this modern era, especially in advanced of engineering materials, it was realize to develop some of non-convectional machining methods known as advanced machining process (AMPs). Laser Beam Machining (LBM) is one of the AMPs that being used nowadays for shaping almost whole range of engineering materials. LBM are widely used for cutting, drilling, marking, welding, sintering, and heat treatment but for this project, this will focus only on cutting. This project is about experimental study of laser beam cutting on acrylic sheet. Cutting experiment will be done on acrylic sheet with thickness of 3mm using PCNC Laser Cutting Machine. The experiment held under some parameters such as cutting angle, cutting speed, laser power, nozzle gap, and air pressure. Response Surface Method (RSM) used to design the experiment which result 40 number of experiment with different values of parameters. The objective of this project is to find the parameter that produced best cutting quality of acrylic sheet. Cutting quality judged by measuring surface roughness of the specimen by using surface roughness tester, MahrSurf XR 20 with Perthometer S2. Two profile parameters that considered in order finding best cutting quality were Roughness Average, Ra and Maximum Roughness Depth, Rmax. From the experiment, the result analyzed and it was found the best cutting quality and parameters that produced that cut. Every parameter has their relationship between each other which affect the quality of cutting. In order to produce better surface, there are some recommendation that can be consider for future research.